Whiteflies (Homoptera: Aleyrodidae) From Central America And Colombia Including Slide-Mounted Pupal And Field Keys For Identification, Field Characteristics, Hosts, Distribution, Natural Enemies, And Economic Importance - Caballero, Rafael De J. (Kansas State University, 1992)
Since the beginning of entomological history, the taxonomy of whiteflies (HOMOPTERA: Aleyrodidae) has been neglected by most taxonomists (Mound and Halsey 1978). Currently, there is no professional systematist employed full time anywhere in the world studying this group (Bink-Moenen and Mound 1990). One common fact concerning whiteflies is the lack of available organized information on their biology, such as habits, ecology, and systematics (Gerling 1990).